Dynamic Modeling of Unmanned Underwater Vehicles with Online Disturbance Compensation Scheme - Sheikh Izzal Azid; Utkal Mehta; Adarsh Kuar; Zahid Ali (Journal of Robotics)
With the advancement in robotics technology over the recent years, underwater robots’ design and development are gaining interest. Unmanned underwater vehicles (UUVs) have many applications in aquaculture, deep-sea exploration, research, and enhanced rescue tasks. However, various factors must be considered when developing any underwater vehicle system to explore the deep ends of the underwater world. In this paper, we develop the most suitable model for understanding various system parameters. The new mathematical model considers certain constraints and external disturbances exerted on the system. Also, a control strategy is suggested for the UUV’s stability and robustness. The suggested observer and model are simple, allowing for accurate estimations of all system states and the global impacts of unknown limped perturbations with a minimal computational cost.